Comparison of the sixth, seventh, and eighth editions of the American Joint Committee on Cancer Tumor-Node-Metastasis staging system for gastric cancer: A single institution experience. Issue 39 (1st October 2021) - Chen, Mei-Wen; Yen, Hsu-Heng
Abstract : Abstract: In 2018, the eighth edition of the American Joint Committee on Cancer Tumor-Node-Metastasis classification and staging system was implemented. Few reports were made comparing the performance of different editions of the American Joint Committee on Cancer (AJCC) system. Therefore, this study aimed to examine the prognostic predictability from the sixth to the eighth editions of the AJCC staging system for gastric cancer. A total of 414 patients with gastric cancer who underwent surgery at Changhua Christian Hospital from January 2007 to December 2017 were enrolled in the study. To identify the prognostic factors for gastric cancer death, univariate and multivariate analyses were performed. The homogeneity and discrimination abilities of the sixth to eighth editions of the staging system were compared using the likelihood ratio chi-square test, linear trend chi-square test, and Akaike information criterion. The sixth edition of the staging system had the lowest Akaike information criterion value, suggesting a better prognostic stratification than other editions. From the result of the likelihood ratio chi-square test, the T and N staging systems of the seventh and eighth editions had better homogeneity and discriminatory ability than the sixth edition. The eighth edition had better prognostic performance in patients at stage III compared with the seventh edition. The AJCC seventh and eighth editions had improved prognostic predictability of the T and N factors compared with the sixth edition. However, the overall staging performance of the eighth edition is not superior compared to the sixth edition. Further studies with larger sample size should be conducted to compare the performance of different editions of the AJCC staging system for different ethnic populations.